2006
DOI: 10.1159/000093631
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Pathogenetics of Renal Cancer

Abstract: Recent developments in genetics and molecular biology have led to an increased understanding of the pathobiology of renal cancer. Thorough knowledge of the molecular pathways associated with renal cancer is a prerequisite for novel potential therapeutic interventions. Studies are ongoing to evaluate novel anticancer agents that target specific molecular entities. This article reviews current knowledge on the genetics and molecular pathogenesis of sporadic and inherited forms of renal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 179 publications
0
12
0
1
Order By: Relevance
“…For several decades, clinicians have observed the limited accuracy and value of the currently used clinicopathological variables and have attempted to search for new specific molecular tissue biomarkers [6, 14]. This study found pS6 for CSS and RFS, and Ki-67 for OS, CSS, and RFS, as significant prognostic markers for survival among the nine selected tissue markers closely related to RCC oncogenesis and tumor progression (p<0.05, Table 3).…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…For several decades, clinicians have observed the limited accuracy and value of the currently used clinicopathological variables and have attempted to search for new specific molecular tissue biomarkers [6, 14]. This study found pS6 for CSS and RFS, and Ki-67 for OS, CSS, and RFS, as significant prognostic markers for survival among the nine selected tissue markers closely related to RCC oncogenesis and tumor progression (p<0.05, Table 3).…”
Section: Discussionmentioning
confidence: 93%
“…This high mortality rate for RCC is due to a lack of confirmed, efficacious therapeutic options for long-term tumor control. The difficulty in developing new treatment for RCC lies in its resistance to radiotherapy, chemotherapy, and immunotherapy [4], intra- and intertumor heterogeneity, and the heterotypic characteristics of pleomorphic RCC histology [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to different available compounds and a growing number of new agents affecting molecularly targeted structures, such as vascular endothelial growth factor (VEGF) and mammalian target of rapamycin (mTOR) signaling [4] an optimal sequence of targeted therapies might exist for patients, potentially increasing survival with mRCC treatment. Although prognostic models, such as the MSKCC (Memorial Sloan Kettering Cancer Center) and Heng scoring systems, have been reported to be independent predictors of clinical outcome, [5], [6] discrimination between outcomes is still limited.…”
Section: Introductionmentioning
confidence: 99%
“…These so-called VEGF-tyrosine kinase inhibitors (VEGF-TKIs) have found wide application, ranging from gastrointestinal stromal tumor (GIST) to medullary thyroid cancer to HCC 16-18 . Clear cell mRCC is a disease particularly susceptible to this mode of angiogenesis inhibition, likely due to aberrations in the von Hippel Lindau ( VHL ) gene that prevent degradation of hypoxia inducible factor (HIF; a VEGF transcription factor) 19-20 . A total of four VEGF-TKIs have been approved for the treatment of mRCC on the basis of positive phase III studies: (1) sorafenib, (2) sunitinib, (3) pazopanib, and (4) axitinib 21-24 .…”
Section: 0 Introductionmentioning
confidence: 99%